Association of Blood Mercury Levels with the Risks of Overweight and High Waist-to-Height Ratio in Children and Adolescents: Data from the Korean National Health and Nutrition Examination Survey - Ky Young Cho (MDPI AG, 2021)
A previous study in adults demonstrated the substantial role of mercury exposure in the development of overweight and obesity. Although children and adolescents are more susceptible to the toxic effects of mercury than adults, studies on the association of overweight and obesity with mercury exposure is limited. This study aimed to investigate the association of blood mercury levels with the body mass index (BMI) and waist-to-height ratio (WHtR) as obesity indices in Korean children and adolescents. The analyzed cross-sectional data were obtained from 1327 participants (age: 10-18 years; 672 male and 655 female) who completed the Korean National Health and Nutrition Examination Survey 2010-2013. The covariates included sociodemographic factors (age, sex, and household income), dietary factors (fish, shellfish, and seaweed consumption), lifestyle factors (alcohol consumption, smoking status, and exercise), and blood hematocrit levels. The adjusted geometric mean blood mercury level was 2.19 µg/L, and the level of mercury was significantly higher in the overweight (BMI ≥ 85th gender and age-specific percentiles) and high WHtR (cutoff: ≥0.5) groups than in the normal group. In all the participants, the blood mercury levels were significantly positively associated with the BMI and WHtR after adjusting for all covariates (p < 0.05). All the participants in the highest blood mercury level quartile were at a higher risk for overweight and a high WHtR than those in the lowest quartile after adjusting for all covariates (p < 0.05). Our study suggests a significant association between mercury exposure and the risks of overweight and high WHtR in Korean children and adolescents.